Gut Microbiome Regulation of Autophagic Flux and Neurodegenerative Disease Risks - Shoubridge, Andrew P.; Fourrier, Célia; Choo, Jocelyn M.; Proud, Christopher G.; Sargeant, Timothy J.; Rogers, Geraint B. (Frontiers in Microbiology, 2021)
The gut microbiome-brain axis exerts considerable influence on the development and regulation of the central nervous system. Numerous pathways have been identified by which the gut microbiome communicates with the brain, falling largely into the two broad categories of neuronal innervation and immune-mediated mechanisms. We describe an additional route by which intestinal microbiology could mediate modifiable risk for neuropathology and neurodegeneration in particular. Autophagy, a ubiquitous cellular process involved in the prevention of cell damage and maintenance of effective cellular function, acts to clear and recycle cellular debris. In doing so, autophagy prevents the accumulation of toxic proteins and the development of neuroinflammation, both common features of dementia. Levels of autophagy are influenced by a range of extrinsic exposures, including nutrient deprivation, infection and hypoxia. These relationships between exposures and rates of autophagy are likely to be mediated, as least in part, by the gut microbiome. For example, the suppression of histone acetylation by microbiome-derived short chain fatty acids appears to be a major contributor to upregulation of autophagic function. We discuss the potential contribution of the microbiome-autophagy axis to neurological health and examine the potential of exploiting this link to predict and prevent neurodegenerative diseases.